Congenital malignant melanoma of the scalp in a 25-day-old neonate. (23rd April 2014) - Enam, Syed Faaiz; Waqas, Muhammad; Rauf, Muhammad Yaseen; Bari, Muhammad Ehsan
Abstract : We present a case of congenital malignant melanoma of the scalp in a neonate. The child was born through caesarean section with a swelling, the size of a tennis ball, on the posterior scalp. At presentation to the clinic at 25 days after birth, the swelling had significantly increased in size and ulcerated. An excision was carried out but, because of extensive haemorrhage and haemodynamic instability, the procedure was limited to subtotal resection. Later on, completion of the excision and flap coverage of the wound were performed. After an initial stable course of a few months, the child came back with local recurrence. A re-excision was planned but the child developed pneumonia resulting in sepsis leading to the demise of the child. The report adds to the literature by describing a rare entity and challenges of managing large vascular scalp lesions with complete excision and defect coverage.